Freely-suspended, single chamber glucose oxidase-laccase enzymatic fuel cell - Asrul, Nurrisa; Othman, Raihan; Yahya, Muhd Zu Azhan; Mohd. Salleh, Hamzah; Yusof, Faridah; Ahmad, Abdul Aziz (Trans Tech Publications, Switzerland, 2012)
We investigate glucose oxidase-laccase EFC employing simplified system design – freely suspended enzymes in a membraneless, single chamber cell. The highly specific enzyme reaction mechanisms permit such system design. The EFC comprises nickel mesh as the oxidative current collector and a carbon-based air electrode as the reductive current collector, enclosed in acrylic casing of 3 ml volumetric capacity. The air electrode also serves as the ambient oxygen diffusion site to continuously feed oxygen into the system. The anolyte consists of glucose oxidase enzyme (10 U), glucose substrate (200 mM) and FAD co-enzyme (3.8 mM), while the catholyte consists of laccase enzyme (10 U) and syringaldazine substrate (216 µM). The cell employing citrate buffer electrolyte of pH 5 exhibits the best characteristics i.e. an open circuit voltage (OCV) around 960 mV and able to sustain continuous discharge current of 30µA for about 31.75 hours. The cell possesses volumetric power density of 286 microwatt/cm3 which is considered comparable to biocatalytic energy systems employing much more complicated design.